PENGARUH SEMANGAT KERJA, HYGIENE FACTOR DAN EMPLOYEE ENGAGEMENT TERHADAP EFEKTIVITAS ORGANISASI PADA PRODI S1 AKUNTANSI UNIVERSITAS PAMULANG - Rini Septiowati; Rakhmawati Oktavianna (EkoPreneur, 2019)
The purpose of this study was to determine the effect of morale, hygiene factors and employee engagement on organizational effectiveness in the accounting department of Pamulang University. The research method used is quantitative research using a questionnaire, this study distributed 77 questionnaires to 77 representatives of several lecturers in the S1 Accounting University of Pamulang whose number of samples was taken by using the Slovin formula. The sample collection technique used is Purposive Sampling. Data analysis in this study was carried out using data quality tests, classic assumption tests, multiple regression analysis, coefficient of determination and hypothesis testing (t & F test).             The results showed that work morale partially influences organizational effectiveness, hygiene factor partially influences organizational effectiveness and employee engagement does not affect organizational effectiveness. While simultaneous work morale, hygiene factor and employee engagement affect the effectiveness of the organization in the S1 Accounting Study Program at Pamulang University. Keywords: morale, hygiene factor, employee engagement, organizational effectiveness.